School districts and their local food supply chains. Issue 3 (7th November 2017) - Christensen, Libby O.; Jablonski, Becca B. R.; O'Hara, Jeffrey K.
Abstract: The 2015 Farm to School Census reports that during the 2013–2014 school year there were over 5200 farm to school (FTS) programs in the USA that involved 39, 000 schools and 24.1 million children. These FTS programs are intended, in part, to increase market access and therefore the viability of farms and ranches. Accordingly, the majority of FTS programs involve local food procurement directly from farmers, from non-traditional suppliers that market locally branded food products such as 'food hubs', or from traditional suppliers such distributors and food service management companies. Yet, there is reason to believe that transaction costs vary based on the supply chain that schools use to procure local food. Moreover, that the supply chain that schools use to procure local food has a relationship with school's expenditures on local food. We use the 2015 Farm to School Census to estimate the relationship between school district's local food expenditures per student and supply chain structure. We analyzed data using ordinary least squares regressions, controlling for the region of the USA, the type of local food products purchased, and other school-specific characteristics. Importantly, we find a negative and significant relationship between school district's non-milk local food expenditure per student, and purchases directly from the farm and from non-traditional suppliers. This implies that schools that purchase local food from traditional distributors are likely to have higher on average expenditures per student compared with schools that purchase local food directly from farmers or non-traditional distributors. Results point to the need for additional research in determining the efficacy of policies to support direct and non-traditional FTS marketing arrangements.